INVESTIGATING THE EFFICACY OF CONTACT LENS CULTURES IN IDENTIFYING PATHOGENS IN KERATITIS CASES: A RETROSPECTIVE COHORT STUDY. - Kumari, Bhawna; Shanker, Shreshth; Kaur, Khushdeep; Sharma, Antaryami (Student’s Journal of Health Research Africa, 2024)
Background The incidence of microbial keratitis, a severe corneal infection, is increasingly prevalent among contact lens users. This study investigates the efficacy of different culture methods in identifying causative pathogens, a critical step for effective treatment, particularly when traditional corneal cultures are inconclusive or unavailable. Methods A retrospective analysis was conducted and involved 60 patients diagnosed with contact lens-related microbial keratitis. The methodology centered on the examination of cultures obtained from corneal scrapings, contact lenses, and lens cases. Additionally, demographic data, clinical treatment, outcomes, and antibiotic susceptibility patterns were analyzed. The data was also analyzed accordingly. Results Findings highlighted a higher rate of pathogen detection in contact lens and lens case cultures (43% and 36.7%, respectively) compared to corneal cultures (20%). The majority of infections were bacterial, with Pseudomonas spp. being the most prevalent. Antibiotic susceptibility testing revealed a high effectiveness of fluoroquinolones and aminoglycosides. Notably, the study observed a post-treatment preference shift from contact lenses to glasses in 60% of patients, indicating the significant impact of the infection on patient lifestyle choices. Conclusion This study underlines the importance of including contact lens and lens case cultures in the diagnostic process for microbial keratitis. The higher yield of pathogens in these cultures suggests their critical role in accurate pathogen identification. Recommendations Early clinical intervention and a comprehensive diagnostic approach are recommended for the effective management of contact lens-related microbial keratitis. Emphasizing patient education on lens hygiene and regular ophthalmological check-ups could also be crucial in prevention strategies.